SOCIAL SUPPORT IN RW LEVEL PKK IN KELURAHAN X - Jonathan Trichristianto; Denny Putra (MANASA, 2017)
Many PKK (Pemberdayaan dan Kesejahteraan Keluarga or Family Empowerment and Welfare) organizations in Jakarta have been rendered inactive due to various reasons, mostly attributed to lack of members, and as a consequence numerous healthcare-related PKK programs are not available to the wider public. Amid this worrying trend however, PKK in certain areas, such as at the RW (rukun warga or community group) level under Kelurahan (urban ward) X, have performed effectively. Social support provided through RW-level PKK has contributed significantly to the well-being of Kelurahan X. This research looks into social support schemes provided under RW-level PKK in Kelurahan X. It is hypothesized that community-level PKK in Kelurahan X provides tremendous social support, especially in terms of emotional, informational and companionship support. This research adopts the quantitative method, gathering data from a census using the Medical Outcome Study: Social Support Survey (MOS-SSS). The research subjects who active PKK members in Kelurahan X are showed high-level social support, especially relating to emotional, informational and companionship support. This finding suggests that RW-level PKK in Kelurahan X has consistently been able to provide much-needed social support to members. It can therefore be implied that local community members are protected from mental and physical illnesses, and lead healthy lives.